Developing the Competencies of Internal Entrepreneurship HR Managers as a Response to the Challenges of Higher Education - Anastasiya PESHA; Marina SHAVROVSKAYA (Communications of International Proceedings, 2021)
Over the past decade, the role and functions of HR managers have undergone significant changes, and their tasks are beginning to include creating a culture that will allow them to find and train internal entrepreneurs in the company. The role of developing such supra-professional competencies as entrepreneurial skills in future personnel management specialists is being strengthened. In this context, universities introduce specialized programs and disciplines aimed at developing students' innovative and entrepreneurial competencies. Based on previous research, the authors identify a list of key entrepreneurial competencies that are important for HR manager as an internal entrepreneur and as a generator of the business development environment in the company. The article presents the results of an empirical analysis of the level of development of entrepreneurial competencies of HR managers in such regions as Yekaterinburg and Sverdlovsk region, Omsk and Omsk region. The results of the study may be interesting to scientists and practitioners who study the assessment and development of entrepreneurial competencies, as well as to teachers who implement training programs for HR managers.
Keywords: Internal Entrepreneurship; Challenges of Higher Education; HR Manager; Supra-Professional Competencies; Entrepreneurial Competencies; HR Management.